1997
DOI: 10.1088/0953-8984/9/30/011
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and temperature electron paramagnetic resonance studies of crystal

Abstract: The effect of temperature and hydrostatic pressure on the spin-Hamiltonian parameter for in elpasolite is studied up to a pressure of 700 MPa over the temperature range 180 - 360 K. It is found that 56% of the temperature change in is caused by the spin - phonon interaction, and the remaining 44% is related to the thermal expansion of the crystal. The temperature at which the phase transition from the cubic to the tetragonal phase occurs is a linear function of pressure, with the pressure coefficient . Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
2
1
0
Order By: Relevance
“…it was found that most of the temperature change in b 0 4 was induced by the spin-phonon interaction, while the remaining was related to the thermal expansion of the crystal [32]. The anomaly, related with both ZFSPs (b 0 2 and b 0 4 ) and distortion parameters, seen here for the both centers between 123 and 213 K is consistent with the suggested phase transition temperatures elsewhere [30][31][32].…”
Section: Temperature Dependence Of Zfsps For Mn 2+ (2)supporting
confidence: 88%
See 1 more Smart Citation
“…it was found that most of the temperature change in b 0 4 was induced by the spin-phonon interaction, while the remaining was related to the thermal expansion of the crystal [32]. The anomaly, related with both ZFSPs (b 0 2 and b 0 4 ) and distortion parameters, seen here for the both centers between 123 and 213 K is consistent with the suggested phase transition temperatures elsewhere [30][31][32].…”
Section: Temperature Dependence Of Zfsps For Mn 2+ (2)supporting
confidence: 88%
“…The anomaly, related with both ZFSPs (b 0 2 and b 0 4 ) and distortion parameters, seen here for the both centers between 123 and 213 K is consistent with the suggested phase transition temperatures elsewhere [30][31][32]. It should be noted that phase transitions would result in drastic changes at the transition temperature in the EPR spectra, such as: line splitting, linewidth or spin Hamiltonian parameters [8].…”
Section: Temperature Dependence Of Zfsps For Mn 2+ (2)supporting
confidence: 86%
“…(ii) The influence of higher-order multiplets on the splittings of ground multiplets 8 S 7/2 is not considered. (iii) The spin-Hamiltonian parameters of a paramagnetic center in crystals at various temperatures stem from two contributions: one is the implicit or static contribution concerning the defect structure of the paramagnetic center and another is the explicit or vibrational contribution due to the electron-phonon interaction [39][40][41][42][43]. The latter is omitted in the calculation.…”
Section: Discussionmentioning
confidence: 99%